Do the Standards of the National Commission for Academic Accreditation& Assessment (NCAAA) Lead to Organization Excellence - Alsaleh, Ghadah (European Scientific Journal, ESJ, 2016)
One way to meet the challenges in creating a high preforming educational institution is the approach of organization excellence. The National Commission for Assessment and Academic Accreditation (NCAAA) was established under the supervision of the Higher Education Council and Ministry of Education in Saudi Arabia to assure the quality standards are applied. This research aims to examine the NCAAA standards based on well-known models for organization excellence that has been used in the education sector. Results show that the NCAAA should focus on some specific areas to assure that excellence of educational is instituted. These areas include: leadership, strategic planning and partnership.